Effectiveness of Butterfly Pea Flower Extract (Clitoria ternatea) as a Natural Alternative Dye to Replace Methyele Blue Diffquick Coloring in Buccal Smear Cytology Preparations - Keisya Nur Raudhah; Ria Amelia; Elfira Maya Sari; Danny Ernest Jonas Luhulima (Jurnal Kesehatan, 2025)
Introduction: Diffquick dying is one the methods of cytological dying. The diffquick method’s components is methylene blue. Methylene blue is toxic and non-biogradable so it requires natural dyes that do not have harmful properties for the body. Clitoria ternatea is a natural colorant that has an anthocyanin content and produces blue pigment and has been tested to color the nucleus of epithelial cells. Method: This research for the influence of temperature factors and long storage of the solution of clit extract as a nutarl colour subtitutes for methylene blue in the coloring of nucleus cells diffquick method. Research design is experimental with purposive sampling. The research was conducted in January-March 2024 at the sitohistotechnology laboratory. Results: The Mann whitney (sig.) test result 1.0>0.05 or H0 was received so there was no difference in the core color power of the cell with a 16% concentration of oak flower extract stored at 7-11⁰C dan 25⁰C as a substitute for the methylene blue dye in diffquick dyeing. Conclusion: This shows that there is no difference in the color power of the cell from the solution of the butterfly pea extract that are stored at showcase and room temperature.